2007
DOI: 10.1111/j.1365-2966.2007.12512.x
|View full text |Cite
|
Sign up to set email alerts
|

The helium abundance and ΔY/ΔZ in lower main-sequence stars

Abstract: We use nearby K dwarf stars to measure the helium-to-metal enrichment ratio Y/ Z, a diagnostic of the chemical history of the solar neighbourhood. Our sample of K dwarfs has homogeneously determined effective temperatures, bolometric luminosities and metallicities, allowing us to fit each star to the appropriate stellar isochrone and determine its helium content indirectly. We use a newly computed set of Padova isochrones which cover a wide range of helium and metal content.Our theoretical isochrones have been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
141
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(170 citation statements)
references
References 201 publications
(359 reference statements)
29
141
0
Order By: Relevance
“…Helium abundances as high as Y ∼ 0.4 are suggested, which for ω Cen imply a helium-to-metal enrichment ratio ΔY /ΔZ 70 (Piotto et al 2005). Such a value is outstandingly larger than that quoted for the solar neighbourhood around and above solar metallicity from a sample of nearby K-dwarf stars, ΔY /ΔZ = 2.1 ± 0.9 (Casagrande et al 2007). Attemps have been made to explain such extreme 4 He abundances in the framework of two main competing scenarios, the so-called 'asymptotic giant branch (AGB) self-pollution scenario' (P. Ventura, this volume) and the so-called 'fast rotating massive star (FRMS) self-pollution scenario' (T. Decressin, this volume).…”
Section: Helium-4mentioning
confidence: 67%
See 2 more Smart Citations
“…Helium abundances as high as Y ∼ 0.4 are suggested, which for ω Cen imply a helium-to-metal enrichment ratio ΔY /ΔZ 70 (Piotto et al 2005). Such a value is outstandingly larger than that quoted for the solar neighbourhood around and above solar metallicity from a sample of nearby K-dwarf stars, ΔY /ΔZ = 2.1 ± 0.9 (Casagrande et al 2007). Attemps have been made to explain such extreme 4 He abundances in the framework of two main competing scenarios, the so-called 'asymptotic giant branch (AGB) self-pollution scenario' (P. Ventura, this volume) and the so-called 'fast rotating massive star (FRMS) self-pollution scenario' (T. Decressin, this volume).…”
Section: Helium-4mentioning
confidence: 67%
“…First of all, it is worth stressing that, when dealing with the evolution of 4 He in the Galactic disc, we can rely on only a few data (see also M. Peimbert et al, this volume), namely, the abundance of 4 He in the Sun at the time of its birth, which is by now quite well established (Asplund et al 2009), the abundance of 4 He in M 17, an H II region located in the inner Galaxy, and the helium-to-metal enrichment ratio as derived from nearby K-dwarf stars. The latter quantity, however, is affected by a rather large error and can only be trusted around solar metallicity (see Casagrande et al 2007 and contribution by L. Casagrande, this volume). Fig.…”
Section: Helium-4mentioning
confidence: 99%
See 1 more Smart Citation
“…Around solar metallicities this analysis yielded ΔY /ΔZ ∼ 2 but at lower Z, Casagrande et al (2007) found that the observed MS is narrower than expected from stellar models computed under this standard ΔY /ΔZ (i.e. the stars are cooler than the isochrones), rather implying a much steeper value of ∼ 10.…”
Section: Introductionmentioning
confidence: 92%
“…More recently, Casagrande et al (2006Casagrande et al ( , 2007 further improved the analysis by compiling a much larger sample of K dwarfs with bolometric magnitudes and effective temperatures derived via InfraRed Flux Method (IRFM). The implementation adopted for the IRFM resorted to homogeneous multi-band photometry to determine in a fully self-consistent, (almost) model independent way T eff and M Bol .…”
Section: Introductionmentioning
confidence: 99%